How Do BRI Narratives and Actions Impact Cooperation Relations and Partnerships Worldwide? - IULIA MONICA OEHLER-ŞINCAI (Global Economic Observer)
- China’s large-scale initiative BRI announced in 2013 first in Kazakhstan, then in Indonesia, detailed in March 2015 and included in the Chinese constitution in October 2017, has become the most intensely discussed and disputed development project worldwide. In the context of actual power shifts, it has been accompanied by both new narratives and actions of countries worldwide but especially in Asia-Pacific and even by the replacement of this denomination with the concept of “Indo-Pacific”, strongly supported by the participants at the Quadrilateral Dialogue (United States-Japan-India-Australia). In only several years, BRI has forged for China solid partnerships with some countries but at the same time it increased the antagonism with others. Taking into account the present context, this paper is focused on finding out how the BRI is influencing the relations between the main actors, situated at the core of global changes.